Differences in Pre-Operative Mean Serum Concentration of Thyroid Stimulating Hormone (TSH) and Free Thyroxin (FT4) in Patients with Benign Thyroid Nodules and Thyroid Carcinoma at Sanglah General Hospital Denpasar - I Gusti Ayu Sri Mahendra Dewi; Desak Putu Gayatri Saraswati Seputra (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Thyroid Stimulating Hormone (TSH) and Free Thyroxin (FT4) concentration are currently highlighted in their relation to thyroid carcinoma development in thyroid nodule patients. This study aimed to identify the difference in the pre-operative mean serum concentration of TSH and FT4 in patients with benign thyroid nodules and thyroid carcinoma at Sanglah General Hospital Denpasar.Methods: : This study was a case-control study that involved 110 patients with thyroid nodules who underwent thyroidectomy at Sanglah General Hospital from January until December 2019, whose specimens were examined histopathologically at the Anatomical Pathology Laboratory of Sanglah General Hospital. Cases were patients with thyroid carcinoma. Controls were patients with benign thyroid nodules. The data were collected from medical records. Results: Most subjects in the thyroid carcinoma group were female (72.7%). The thyroid carcinoma group had a higher mean age at the time of thyroidectomy (47.33 ± 13.4) compared to the benign thyroid nodule group (46.07 ± 12.5) (p = 0.61). Significant difference was found regarding the nodule size between the two groups (p < 0.001). There were no significant differences in terms of nodule lateralization (p = 0.56) and the number of nodules (p = 0.58). Papillary thyroid carcinoma was the most common type of thyroid carcinoma (89.1%). A significantly higher pre-operative mean serum TSH concentration was found in cases (1.0 ± 0.23 IU/mL) compared to controls (0.8 ± 0.23 IU/mL) (p < 0.001). The pre-operative mean serum FT4 concentration was significantly lower in cases (1.1 ± 0.25 IU/mL) compared to controls (1.2 ± 0.22 IU/mL) (p = 0.006). The optimal TSH and FT4 cut-off values for thyroid carcinoma were > 1.0 IU/mL (61% sensitivity, 71% specificity) and < 1.1 IU/mL (61% sensitivity, 51% specificity), respectively Conclusions: : Higher pre-operative mean TSH concentration and lower mean FT4 concentration were found in patients with thyroid carcinoma. There were statistically significant differences between patients with thyroid carcinoma and benign thyroid nodules in terms of these two laboratory parameters.